Time-related aspects of commute well-being - Sandberg Birgitta; Hurmerinta Leila; Leino Henna M.; Lehtonen Esko; Lyytimäki Jari (Elsevier (Commercial Publisher), 2025)
Commute well-being is a multidimensional concept. However, existing research on commuting has focused mainly on hedonic well-being, whereas eudaimonic well-being has been given very little consideration. Furthermore, even though the time-related aspects of commute well-being have been acknowledged in conceptual studies, empirical studies have not yet explored them. The aim of this study is to understand both hedonic and eudaimonic dimensions of commute well-being and how these are shaped by time-related aspects relating to the past, present and future. An exploratory qualitative study was conducted using semi-structured interviews with 108 individuals representing commuters from three different working environments. Data was coded inductively, and the analysis revealed reflections on past commuting, rewards from present-day commuting and long-term justifications of commuting decisions. The study shows how issues related to eudaimonic well-being establish the long-term base of commuting behaviour and how past hedonic commute well-being impacts commuting behaviour. Acknowledging the temporal dimension is important, because inducing long-lasting behavioural changes requires an understanding of the past and present hedonic commute well-being experiences that impact commuting behaviour in the future. Eudaimonic well-being affects commuters over a longer timescale and enables them to live contently with their choices in the long term.